Annexin A10 expression correlates with serrated pathway features in colorectal carcinoma with microsatellite instability. Issue 12 (7th June 2014) - Kim, Jung Ho; Rhee, Ye‐Young; Kim, Kyung‐Ju; Cho, Nam‐Yun; Lee, Hye Seung; Kang, Gyeong Hoon
<x xml:space="preserve">Abstract</x> Annexin A10 (ANXA10) has recently been identified as a marker of sessile serrated adenomas/polyps of the colorectum. Although the serrated neoplasia pathway is thought to be involved in the majority of microsatellite instability‐high (MSI‐H) sporadic colorectal carcinomas (CRCs), the clinicopathological implications of ANXA10 expression in CRC are unknown. Here, we evaluated ANXA10 expression status in 168 MSI‐H CRCs by immunohistochemistry. Among 168 MSI‐H CRCs, nuclear staining for ANXA10 in tumor cells revealed 28 cases (17%) with ANXA10‐positive (ANXA10+) tumors. Most of the ANXA10+ tumors were located in the proximal colon (96%, p < 0.001). The ANXA10+ phenotype in MSI‐H CRC was significantly associated with female gender (68%, p = 0.016), CpG island methylator phenotype‐high (CIMP‐H) (68%, p < 0.001), MLH1 promoter hypermethylation (61%, p < 0.001), loss of MLH1 expression (82%, p = 0.019), and wild‐type KRAS status (96%, p = 0.023). Survival analysis revealed no prognostic significance of ANXA10 expression in MSI‐H CRC. In conclusion, ANXA10+ MSI‐H colon carcinomas are characterized by serrated pathway features, including proximal location, female predominance, and high frequencies of CIMP‐H status and MLH1 methylation.